Oral cancer awareness among male adolescent population in Kanpur, Uttar Pradesh: a systematic review - Sourav Goswami; Jagruti Bhattacharjee (International Journal Of Community Medicine And Public Health, 2026)
Oral cancer is one of the most common cancers in India and constitutes a major public health challenge. Tobacco use, areca nut consumption, smoking, alcohol use, and poor awareness regarding oral cancer contribute significantly to disease burden. Adolescents are particularly vulnerable because many risk-related behaviours begin during this period of life. Understanding the level of oral cancer awareness among male adolescents is essential for designing effective preventive interventions. Objectives were to systematically review the available literature on oral cancer awareness among male adolescents, with a focus on evidence relevant to Kanpur, Uttar Pradesh, and comparable Indian populations. A systematic review of published literature was conducted using electronic databases including PubMed, Google Scholar, Scopus, and Web of Science. Studies published in English between 2010 and 2025 assessing oral cancer awareness, knowledge of risk factors, symptoms, prevention, and screening among adolescents were included. Relevant studies conducted in India and similar socio-cultural settings were critically appraised and synthesized narratively. The review identified consistently low to moderate levels of oral cancer awareness among adolescents. Knowledge regarding tobacco as a risk factor was relatively common, whereas awareness of smokeless tobacco, areca nut products, early signs of oral cancer, and the importance of regular oral examinations was considerably lower. School-based educational interventions demonstrated significant improvements in awareness and preventive attitudes.